Employment of Business Ethics Typology to Measure Influence of Owner Support, Ethical Climate and Career Success on Job Satisfaction within Small Medium Enterprises in Indonesia - Muhammad Idrus Taba; Julius Jillbert; Mahlia Muis; Siti Haerani; Andi Rahmawati (IECON: International Economics and Business Conference, 2023)
Organizational ethics influence the formation of a good environmental atmosphere for all members of the organization. The application of ethics in the organization will be able to increase employee job satisfaction. The purpose of this research is to investigate the relationship between organizational ethics and job satisfaction in small and medium enterprises(SMEs) in South Sulawesi. This study was analyzed using the multiple regression method by taking research objects from 350 SME actors in three districts, namely East Luwu, Bone, and Tana Toraja in South Sulawesi. This research is built from three ethical concepts on typology,namely the climate of egoistic ethics, the climate of kindness ethics, and the climate of principled ethics. The results of the study found that there was no effect of top management support for ethical behaviour on job satisfaction. Individual efforts in finding suitability with the work environment create space so that the relationship does not show significant value. Theethical climate with job satisfaction shows a significant and positive value, but the egoistic ethical climate gets the lowest score. Conversely, a climate of benevolence (kind), gives effect employee awareness which creates a sense of satisfaction. Ethics of company behaviour in career success has a significant and negative effect on job satisfaction. Career ethics that are valued or not appreciated, have the opposite effect on the level of job satisfaction. The researchimplies that the results of mapping ethical values and satisfaction can be in the form of a codeof ethics in business that reflects employees' ideas and organizational cultural values which canbe taught in Business Ethics courses at all levels of higher education.